Relationship Between Postnatal Depression of Mental Health Patients and the Psychological Health of Their Offspring - Abd Rahman, Fairuz Nazri; Wong, Yun Yaw; Khalib, Ahmad Qabil (Frontiers in Psychiatry, 2022)
Postnatal depression is a major illness affecting maternal and family health. The rate of postnatal depression among mental health clients is postulated to be higher than in the community due to the added brain assault. Children of parents who are mental health clients are more likely to have psychological problems compared to children from other parents in the community. This study investigates the rate of postnatal depression among mental health clients and their offspring's psychological health. A total of 140 mental health clients were assessed using the Edinburgh Postnatal Depression Scale. They subsequently completed the Strength and Difficulties Questionnaire regarding their children. The majority ethnicity was the Kadazan (40.7%). The mean age of mothers was 38.6 (7) years with most having a secondary education (53.6%) and a household income per month of less than RM1000 per month (27.1%). The postnatal depression rate was 47.8 %. Higher EPDS scores were associated with higher total SDQ scores in their offspring. Model 1 was unadjusted, giving an OR of 5.65 (95% CI (3.74, 7.55)), p<0.001. After adjustment for confounders, Model 2 had an OR of 5.51 (95% CI (3.57, 7.46)), p<0.001. More efforts need to be given to the early detection of maternal depression and its prompt treatment in mental health clients because of the relationship with the psychological health of the offspring.